FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK REKLAME DENGAN PDRB SEBAGAI VARIABEL MODERATING DI KABUPATEN MAGETAN - Dina Dwi Fitriana; M.Agus Sudrajat (INVENTORY: JURNAL AKUNTANSI, 2017)
This study aims to determine the effect of the population, the number of industries and the number of SIUP on advertisement tax acceptance. And, to know the influence of these variables with PDRB as a moderation variable. The population in this study is the population, the number of industries, and the number of SIUP every year. Sampling in this research using Purposive Sampling. The number of samples in this study as much as 6 years. Hypothesis testing using multiple linear regression analysis. The result of the research shows that: (1) Partially, the number of population has no significant positive effect on advertisement tax acceptance, the variable of the number of industries has a significant positive effect on advertisement tax acceptance, and SIUP amount negatively affect advertisement tax acceptance. (2) GRDP weaken the relation of population to advertisement tax acceptance, PDRB also weaken the correlation of industry amount to advertisement tax acceptance, and PDRB strengthen the relation of SIUP amount to advertisement tax revenue.Keywords: Number of Population, Number of Industry, Number of SIUP, GRDP, Advertising Tax.